ANGELS & DEMONS - Brown, Dan, 1964-, author 274722 (New York : Pocket Star Books, 2000)
World-renowned Harvard symbologist Robert Langdon is summoned to a Swiss research facility to analyze a cryptic symbol seared into the chest of a murdered physicist. What he discovers is unimaginable: a deadly vendetta against the Catholic Church by a centuries-old underground organization, the Illuminati. Desperate to save the Vatican from a powerful time bomb, Langdon joins forces in Rome with the beautiful and mysterious scientist Vittoria Vetra. Together they embark on a frantic hunt through sealed crypts, dangerous catacombs, deserted cathedrals, and the most secretive vault on earth, the long-forgotten Illuminati lair.